Daya Tolak Ekstrak Metanol Daun Kesum (Polygonum minus Huds.) Terhadap Lalat Rumah (Musca domestica L.) - Ari Hepi Yanti, Elisa Kumalasari, Tri Rima Setyawati, (Universitas Tanjungpura, 2015)
One of the ways of controlling the housefly (Musca domestica L.) is by using botanical insecticide that is capable of repelling M. domestica i.e. using the kesum leaf (Polygonum minus Huds.). This research aimed to determine the lowest concentration of methanol extract of P. minus that had a repellent effect, as well as to determine the effectiveness of the extract in causing knockdown and its first knockdown period on M. domestica. The research was conducted from January to February 2014 at the Laboratory of Zoology, Faculty of Mathematics and Natural Sciences and the Laboratory of Forest Products Technology, Faculty of Forestry, Tanjungpura University. This research uses a Randomized Group Design (RGD) in which there were 6 treatments of electric mats with active ingredient of methanol extract of P. minus with concentrations of 5%, 10%, 15%, 20% and 25% respectively, as well as alcohol of 50% as a solvent control, which was repeated 3 times. The test results indicated that the methanol extract of P. minus had a repellent effect and knockdown against M. domestica, where the concentration of the methanol extract of P. minus at 10% offered the highest repellent effect by 61.67% which fell into the moderate category and concentration of the extract at 25% was more effective in causing knockdown against M. domestica by 75% where the first knockdown period occurred in the 40th minute.